Under occupation : a novel - Furst, Alan (Random House, 2019)
"After the Nazi victory over Poland in 1939, thousands of Poles were sent to Germany as slave laborers. From inside enemy territory, they found ways to get valuable information to resistance fighters in France. Paul Ricard, a French writer of detective novels, is drawn in to working in the resistance, as a spy against the Reich, and is charged with getting the information from the Polish prisoners to the Allied forces. Alongside him in the fight against Germany are an émigré girl and a mysterious Turkish woman who is in the contract espionage business."--